Effect of bonded length on the load response and failure mode of pull-out tests of GFRP bars embedded in concrete. (12th September 2022) - Zhao, Xudong; Minhajur Rahman, Mohammod; D'Antino, Tommaso; Focacci, Francesco; Carloni, Christian
Highlights: The stress transfer mechanism occurs within the superficial layer of resin. The free end of the bar slips prior to attaining the peak load. Load when the free end starts to slip and bond strength depend on bonded length. Oscillations in the load are associated with the presence of a carbon fiber yarn. Peak load versus bonded length is compared with the ACI 440.1R-15 formula. Abstract: In this paper, the experimental results of pull-out tests of glass fiber-reinforced polymer (GFRP) bars embedded in concrete are presented and discussed. The experimental work is designed to investigate the effect of the bonded length on the bond behavior of the bars. Five bonded lengths are considered. The first bonded length is equal to 5 times the bar diameter ( db ), which is the bonded length recommended in ASTM D7913. The other four bonded lengths are equal to 10 db, 20 db, 30 db, and 40 db . Loaded-end displacement is obtained from the measurements of three linear variable displacement transformers (LVDTs). Pull-out tests are performed in displacement control. For some specimens, the free-end displacement is measured by two additional LVDTs. The load responses in terms of applied load versus machine stroke, loaded-end slip, and free-end slip are plotted and compared for the different bonded lengths. The average shear stress is plotted versus the bonded length. Finally, the maximum axial stress in pull-out tests is plotted versus the bonded length and compared with the prediction of ACI 440.1R-15.